A 2000 year midge-based paleotemperature reconstruction from the Canadian Arctic archipelago - Porinchu, D.; MacDonald, G.; Rolland, N. (Journal of Paleolimnology, 2009)
A lake sediment core recovered from Lake V57 on Victoria Island, Nunavut, Canada, spanning the last 2000 years, was analyzed for sub-fossil midge remains and organic-matter content (estimated by loss-on-ignition (LOI)). Significant changes in midge community composition occurred during the last 2000 years, with a distinct midge community appearing after 1600 AD. The chironomid community between 0 and 1600 AD was dominated by Heterotrissocladius, Tanytarsus, Abiskomyia, and Paracladius. At approximately 1600 AD, Heterotrissocladius decreased in relative abundance and taxa such as Corynocera ambigua, C. oliveri, Psectrocladius sordidellus type, and Pentanneurini increased in relative abundance. Previously published midge-based inference models for average July air temperature (AJAT) and summer surface-water temperature (SSWT) were applied to the subfossil midge stratigraphy. The AJAT reconstruction indicates relatively cool conditions existed between 1100 and 1600 AD, with exceptional warming occuring after 1600 AD, as lake productivity inferred from organic-matter content increased concomitantly with midge-inferred AJAT and SSWT. The cooler conditions between 1200 and 1600 AD, and the pattern of warming over recent centuries inferred from Lake V57 is broadly consistent with temperature-sensitive biogenic silica records from other sites in the central Canadian Arctic and the treeline zone to the south suggesting a regionally synchronous response to climate forcing.
id: 1863; 395EF Times Cited:3 Cited References Count:57Y